Role of Supply Chain in the Implementation of Multi-Month Dispensing of Antiretroviral among People Living with Human Immunodeficiency Virus in Tanzania (Tanzania Medical Journal, 2022)
BackgroundGlobally, it is estimated that by 2020 28.2 million of all people living with HIV were accessing antiretroviral (ARV) therapy. Providing Multi-Month Dispensing (MMD) of ARV for stable clients has been reported to increase adherence and improve health outcomes in terms of death, retention, adherence, immunosuppression, and viral suppression. The objective of this study was to investigate the role of the health commodities supply chain in the implementation of MMD among people living with Human Immuno Deficiency Virus (HIV) in Tanzania.MethodsThis was a mixed-method cross-sectional study, to investigate the role of the supply chain in the roll-out of the MMD strategy. The study was carried out in 44 Care and Treatment Clinics (CTC) in Mtwara, Lindi, Morogoro, Iringa, Njombe and Ruvuma regions. A structured electronic questionnaire was administered to CTC in-charges and key informant interviews were conducted with 14 District Pharmacists. STATA software version 15 was used for quantitative data analysis and NVIVO 11 was used for qualitative data analysis.ResultsMajority of the health facilities 95.4% had enough first-line ARV medications; 59.1% had enough stock of second-line medications 70.4% had enough stock of paediatrics regimens to support MMD implementation. ARV related factors contributed to 36% of the most common challenges attributed to poor implementation of MMD (ARV stock (23%) and ARV shortage (13%)).. This study established that, the solution of running out of ARV stock is to ensure that ordering is timely done, using quality data and whenever need be, redistribution from nearby facilities to ensure uninterrupted supply of ARVs. ConclusionARV supply chain is at the core of the successful implementation of MMD. The supply chain of ARV drugs should be thoroughly reviewed to ensure ARV resupply is processed timely for all health facilities to maintain appropriate stock levels. To realise and sustain MMD goals.